Resistance Profile of Gram Negative Bacilli in Diabetic Ulcers to Meropenem and Imipenem Antibiotics - Saputri, Fadhilah Nur Amalia; Hanifah Zulkarnaen; Ardy Prian Nirwana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Increasing resistance of Gram-negative bacilli to carbapenems poses a serious threat to diabetic ulcer management. This descriptive cross-sectional study aimed to determine the resistance profiles of Gram-negative bacilli isolated from diabetic ulcers against imipenem and meropenem. Pus samples form 20 patients were identified via biochemical tests and subjected to sensitivity testing using the Kirby-Bauer disk diffusion method (CLSI M100 Ed. 35 standards). The result Pseudomonas aeruginosa (40%) as the predominant species. Susceptibility testing revealed that P.aeruginosa exhibited resistance to meropenem (63%) compared to imipenem (37.5%), while Eschericia coli and Enterobacter aerogenes showed complete resistance resistance (100%) to both antibiotics. In conclusion, Gram-negative bacilli in the study demonstrated better susceptibility to imipenem than meropenem, suggesting imipenem as a potentially more effective option for empirical therapy. These finding semphasezi the critical need for pariode surveillance and strict antibiotic stewardship to pravent further escalation of carbapenemn resistance in diabetic care settings.